Relationship Satisfaction among South Asian Canadians: The Role of ‘Complementary-Equality’ and Listening to Understand - David W. Reid; Saunia Ahmad (Interpersona: An International Journal on Personal Relationships, 2008)
This study explored the ways in which adherence to traditional marital expectations in ones marriage was related to styles of interpersonal listening and marital satisfaction among Indo-Pakistanis living in a Western country. Participants (n = 114) were recruited from a large metropolitan city in Canada, were married, and their ages ranged from 19 to 67 years. They completed measures of marital satisfaction, listening styles, and traditional orientation to marriage. Results indicated that greater adherence to traditional marital beliefs were correlated with lower levels of interpersonal listening and marital satisfaction. However, closer examination of the traditional orientation subscales revealed that expectation of traditional husband and wife roles did not result in lower empathic listening in one’s marriage or lower marital satisfaction, but the lower degree to which one believed in upholding equality in undertaking such traditional roles did. Furthermore, empathic listening mediated the relationship between belief in equality in one’s relationship and marital satisfaction. The implications of these results for enhancing relationship satisfaction for Indo-Pakistanis are discussed.